2021
DOI: 10.3389/fmed.2021.658058
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Characteristics of a Community-Acquired Carbapenem-Resistant Escherichia coli ST410 Isolate Harbouring blaNDM-5-Encoding IncX3-Type Plasmid From Blood

Abstract: Objectives: The aim of this research was to investigate the clinical and microbiological characteristics of a case of community-acquired carbapenem-resistant Escherichia coli isolated from a patient with a bloodstream infection in China.Methods:Escherichia coli Huamei202001 was recovered from the first blood culture from a patient hospitalised in China. An antimicrobial susceptibility test was performed, and the genome was sequenced on an Illumina HiSeq X 10 platform with a 150-bp paired-end approach. The gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Escherichia coli strains that are ST410 are widely distributed in Europe (Poland, 29 Denmark, 30 Italy, 31 etc. ), Asia (South Korea, 32 Singapore, 33 India, 34 China, 35 etc. ), Africa, 36 North America (United States, 37 Mexico, 38 etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains that are ST410 are widely distributed in Europe (Poland, 29 Denmark, 30 Italy, 31 etc. ), Asia (South Korea, 32 Singapore, 33 India, 34 China, 35 etc. ), Africa, 36 North America (United States, 37 Mexico, 38 etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The carbapenemase resistance gene bla NDM−5 was detected in one of the three carbapenem-resistant strains, and the other two strains were ESBLs-producing. Two carbapenemases, KPC and NDM, were responsible for phenotypic resistance in 90% of the carbapenem-resistant Enterobacteriaceae ( 30 ). Studies unveiled many distinguishing features for their successful persistence and spread ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 While Gu's study suggested that CPECO strains in blood cultures might originate from intestinal colonization strains, as they had highly similar PFGE fingerprinting. 16 Previous studies had also shown a higher rate of CRE infection in patients who were CRE intestinal colonization carriers compared to non-CRE colonization patients. 17 We hypothesized that the probable pathway of CPECO infection in patients with biliary system diseases involved the translocation of CPECO strains from the intestinal tract, particularly with the assistance of certain invasive procedures, such as ERCP surgery, which might accelerate the occurrence of translocation and infection.…”
mentioning
confidence: 96%